CIVILIZATIONAL AND INSTITUTIONAL ASPECTS OF NATIONAL SELF-IDENTIFICATION IN UKRAINE: PHILOSOPHICAL-ANTHROPOLOGICAL APPROACH - M. I. Boichenko; O. V. Yakovleva; V. V. Liakh (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. This article clarifies the significance of the person’s social self-identification as a basis for civilization and institutional explanation of national self-identification in Ukraine. Theoretical basis. The authors found that the analysis of the cultural and anthropological principles of national self-identity reveals two main opposed concepts: the concept of "eastern" cultural and social self-identity of Ukraine, which correlates with the metaphor of the split between "East" and "West", and the concept of "western" projection of the European future of Ukraine, which correlates with the metaphor of the bridge between "East" and "West". These concepts reflect the options for the citizens of Ukraine to make a personal choice of the way in achieving social self-identity. Douglas North’s concept of "open-access order" states and "limited access order" states can be used as a basis for an alternative, pragmatic approach to choice the criteria of national self-identity. Originality. National self-identification is a result of the choice of the person’s self-identification: still the person takes into account the history of the nation, the ethnic diversity of the nation, its cultural and civilizational characteristics. The philosophical-anthropological approach contributes to the demystification of the grounds of social self-identification, revealing the decisive role of the personal choice in shaping the new institutional foundations of national self-identity. Harmonization of the social institutions of Ukraine with the institutions of the European Union and the international community institutions opens wide opportunities for Ukraine’s successful integration into the "open-access order" societies. The clarification of the value and symbolic aspects of national self-identity in Ukraine contributes to the successful functioning of these institutions. Multilingualism is an adequate response to the global challenge of the reconstruction of Ukraine’s national self-identity. The education system is a key area for introducing multilingualism. Conclusions. The development, justification and systematization of cultural and institutional criteria for choosing the best ways to strengthen of national self-identity in Ukraine are a prerequisite for the successful self-identification of Ukrainian citizens in a complex and ever-changing global world.